Virtual Reality Reduces Pain in Laboring Women: A Randomized Controlled Trial - Wong, Melissa S.; Spiegel, Brennan M.R.; Gregory, Kimberly D. (American Journal of Perinatology, 2020)
Objective Virtual reality (VR) represents a potential method for easing labor pain and in nonpregnant patients has been shown to achieve similar or greater analgesia than hydromorphone. Few studies of VR have been performed in pregnant women. The aim of this randomized controlled trial (RCT) is to evaluate whether VR is effective in reducing pain in laboring women.Study Design An open-label, RCT of nulliparous, term women in labor in a tertiary care hospital. We included women with a pain score level of 4 to 7 having regular contractions at least every 5 minutes. We excluded women who had received any pharmacologic pain relief including neuraxial analgesia and those with contraindications to VR. Participants were randomized to up to 30 minutes of either VR or the control arm (no additional intervention). Our primary outcome was the difference in differences from pre- to postintervention pain score. Prespecified secondary outcomes included postintervention pain scores, duration of intervention use, pharmacologic analgesia use, maternal vitals, and obstetric outcomes.Results From March 2018 to February 2019, 40 subjects were enrolled, randomized, and completed the study; 19 were randomized to control and 21 to the VR arm. Most baseline characteristics were similar between groups. For the primary outcome, those assigned to the control arm had a statistically significant increase in pain of +0.58, while the VR arm had a significant reduction in pain of −0.52 (p = 0.03). There was also a difference in the proportion who had a minimum clinically important difference in pain (0% control and 23.8% VR; p = 0.049). Postintervention maternal heart rate was higher in the control arm (86.8 vs. 76.3, p = 0.01). Most other secondary outcomes did not differ.Conclusion In our study, we found that VR was effective for reducing pain in women in labor as compared with those receiving no intervention.Key Points
Keywords: labor; pain; analgesia; anesthesia; virtual reality; complementary alternative medicine